Moral judgment and self-esteem in school students of the fifth year of secondary schools in Lima Metropolitana - Vargas G., Julia (2016)
This research raises as a problem the relationship between self-esteem and moral judgment fifth graders of secondary schools in metropolitan Lima. The central hypothesis formulated is the relationship between the score of moral judgment and self-esteem score. The simple consisted of 400 students between 16 and 17, male and are in fifth year of high school, from three schools in metropolitan Lima consists of: two private and one state. They answered a Sociomoral Reflection Test (SROM) of Gibbs and Widaman and Coopersmith and Self-Esteem Inventory of Coopersmith. The research design was correlational. The results indicate that there are significant differences in moral judgment and self-esteem among state colleges and private colleges. The private colleges had more score. The conclusion was also found that there is significant positive correlation between self-esteem and moral judgment.